(untitled) (Research, Society and Development, 2025)
Introduction: Parkinson’s Disease (PD) is a progressive neurological condition, marked by degeneration of neurons in the substantia nigra, and manifested by motor symptoms (such as musculoskeletal and neuromuscular alterations) and non-motor symptoms (including sensory, cognitive and perceptual alterations). Objective: to analyze the effects of a neurofunctional rehabilitation protocol on balance, coordination and muscle tone in a patient with PD. This study involved a 50-year-old male patient diagnosed with PD 8 years ago, presenting with mild resting tremor, hypertonia in the right upper limb, a Hoehn and Yahr scale score of 1.5, 21 points on the UPDRS and 30 points on the SBP. The intervention consisted of 10 weekly sessions, initially using gametherapy with the Kinect Adventure® game on the Xbox 360®, promoting limb mobility, postural shifts and agility. This was followed by balance training with dual tasks and functional reach, ending with a functional circuit and motor tasks. Qualitative assessments were carried out at each session and, at the end, the UPDRS and PAS scales were reassessed. Results: There was an improvement in upper limb range of motion, agility, gait, balance and postural control. Conclusion: The protocol was effective in promoting motor and non-motor functional gains, with emphasis on engagement and body control during gamete therapy.